USE OF AN INTRAVENOUS IMMUNOGLOBULIN IN NORMALIZATION OF REACTIONS OF GU-MORAL AND CELLULAR IMMUNITY AT OFTEN ILL CHILDREN SHARP RESPI-RATORNYMI VIRUS INFECTIONS WITH A SYNDROME LYMPHADENOPATHY - Popov, N. N.; Savvo, A. N.; Koliushko, E. G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The purpose of the present research was studying of efficiency of application of an intravenous immunoglobulin in treatment of often ill children by sharp respiratory virus infections with a syndrome lymphadenopathy. The obtained data specifies that application ВВИГ allows about treatment terms, in 3 times reduces disease DRS within a year, warns development of bacterial complications, liquidates lymphadenopathy. At children receiving VVIG, dynamical increase of local and system immunity, activization of anti-virus immunity, normalization of funktsional th activity of lymphocytes and phagocytes cages is observed. Under the influence of VVIG spontaneous and IL-2-induction proliferative activity of lymphocytes, and also spontaneous production IL-2 and IL-10 at patients decrease to normal values. The offered therapy allows to normalize in short terms it-munnye processes with which development of lymphadenopathy associates.